A Regioselective Approach to C3-Aroylcoumarins via Cobalt-Catalyzed C(sp2)–H Activation Carbonylation of Coumarins - Pashazadeh, Rahim; Rajai-Daryasarei, Saideh; Mirzaei, Siyavash; Soheilizad, Mehdi; Ansari, Samira; Shabanian, Meisam (Synthesis, 2019)
A new cobalt-catalyzed C–H bond activation of coumarins with aryl halides or pseudohalides and carbon monoxide insertion to give various 3-aroylcoumarin derivatives is described. It is the first time that CO as C1 feedstock is used as the coupling partners in cobalt-catalyzed regioselective coumarin C–H functionalization reactions. Upon activation with manganese powder, the Co catalyzes the C–H bond activation carbonylation reactions of aryl iodides, bromides, and even triflates under mild conditions, providing the regioselective aroylated products in moderate to good yields.
Keywords: cobalt-catalyzed; C–H activation; carbon monoxide; carbonylation; 3-aroylcoumarin